O pewnych wspólnych cechach IX-wiecznej ceramiki z obszaru północnej i południowej części obecnego Dolnego Śląska - Gruszka, Bartłomiej; Pankiewicz, Aleksandra (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2016)
This article presents the results of comparative research into 9th century vessels discovered in numerous archaeological sites in Lower Silesia. The research was underpinned with petrographic analyses of ceramics representing a progressive trend in pottery. The reason why this issue is discussed is the occurrence of vessels with similar technological and stylistic attributes in both the south and the north of the region under scrutiny. The research leads to a conclusion that the common features shared by the ceramics artefacts may result from foreign influences in the north and the south of the region alike. However, numerous similarities in the final touches of the vessels indicate that in the first half of the 9th century (if not later), Silesian potters shared their experiences while the populations of the north and the south of the region and exchanged various artefacts including vessels. This exchange of experience in pottery production bore fruit in the form of stylistically and formally diverse vessels.